Analisis Kinerja Protokol Routing Social Aware Berbasis Konten Pada Opportunistic Network - Ricky Yonas; Bambang Soelistijanto (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Opportunistic Networks (OppNet) is one of Delay Tolerant Network (DTN) application. It is a wireless communication that is not require any infrastrusture thus, the difference between OppNet and conventional cellular communication is obvious. In OppNet, nodes are communicating via other node’s radiowave (in this case, we used Bluetooth). Messages are handed over node by node until it reaches its destination node. In social aware routing protocol, social weights are given to each node. Social weights will determine node’s movement and it’s transitivity or even it’s community to help messages reachs it’s destination faster. With transitivity, the delivery probability can reach an optimum number of 80%, that means in every 10 messages, 8 messages are successfully delivered.